2008
DOI: 10.1007/s11010-008-9701-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in primary glomerular diseases: a comparative study

Abstract: Oxidative stress in PGN is significantly higher than NPGN, indicating higher oxidative stress in these patients, independent of degree of renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Oxidative stress is a phenomenon associated with pathogenetic mechanisms of several diseases, including atherosclerosis, cancer, diabetes mellitus and inflammatory diseases, as well as with aging processes. The levels of oxidative stress markers in plasma and urine, especially of 8-isoprostane, HNE and MDA, reportedly reflect systemic production in diseases such as diabetes 7) , hypertension 8) and renal diseases 9) .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is a phenomenon associated with pathogenetic mechanisms of several diseases, including atherosclerosis, cancer, diabetes mellitus and inflammatory diseases, as well as with aging processes. The levels of oxidative stress markers in plasma and urine, especially of 8-isoprostane, HNE and MDA, reportedly reflect systemic production in diseases such as diabetes 7) , hypertension 8) and renal diseases 9) .…”
Section: Introductionmentioning
confidence: 99%
“…Markan et al (3) showed that pro-oxidant markers (malondialdehyde, 8-isoprostane, total homocysteine) were significantly higher and antioxidant markers (superoxide dismutase) were significantly lower in primary GN patients compared to the control subjects. When patients were grouped as PGN and NPGN; OS was shown to be significantly profound in the PGN group compared with NPGN group (3).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, immunologic injuries are localized to the mesangium or subendothelial space directly in contact with the circulation in PGN. In addition to urinary findings, a marked inflammatory response may cause an increased level of reactive oxygen species (ROS) in PGN compared to NPGN (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markan et al (3) showed that pro-oxidant markers (malondialdehyde, 8-isoprostane, total homocysteine) were significantly higher and antioxidant markers (superoxide dismutase) were significantly lower in primary GN patients compared to the control subjects. When patients were grouped as PGN and NPGN; OS was shown to be significantly profound in the PGN group compared with NPGN group (3).…”
Section: Discussionmentioning
confidence: 99%